Effects of Organic and Inorganic Materials on Soil Acidity and Phosphorus Availability in a Soil Incubation Study. (8th July 2012) - Opala, P. A.; Okalebo, J. R.; Othieno, C. O.
Abstract : We tested the effects of two organic materials (OMs) of varying chemical characteristics that is, farmyard manure (FYM) and Tithonia diversifolia (tithonia), when applied alone or in combination with three inorganic P sources, that is, triple superphosphate (TSP), Minjingu phosphate rock (MPR), and Busumbu phosphate rock (BPR) on soil pH, exchangeable acidity, exchangeable Al, and P availability in an incubation study. FYM and tithonia increased the soil pH and reduced the exchangeable acidity and Al in the short term, but the inorganic P sources did not significantly affect these parameters. The effectiveness of the inorganic P sources in increasing P availability followed the order, TSP > MPR > BPR, while among the OMs, FYM was more effective than tithonia. There was no evidence of synergism in terms of increased available P when organic and inorganic P sources were combined. The combination of OMs with inorganic P fertilizers may, however, have other benefits associated with integrated soil fertility management.